2014
DOI: 10.3109/10428194.2014.894189
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia risk by industry and occupation

Abstract: Acute myeloid leukemia (AML) is the most common type of leukemia found in adults. Identifying jobs that pose a risk for AML may be useful for identifying new risk factors. A matched case–control analysis was conducted using California Cancer Registry data from 1988 to 2007. This study included 8999 cases of AML and 24 822 controls. Industries with a statistically significant increased AML risk were construction (matched odds ratio [mOR] = 1.13); crop production (mOR = 1.41); support activities for agriculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Leukemia mortality was reported to be significantly elevated for several white collar occupations in Washington State, including purchasing agents, buyers managers, sales representatives, and insurance agents during 2000–2010 [Milham and Ossiander, ]. A small New Zealand case‐control study reported that risk was not elevated in administrators and other occupations [McLean et al, ]; and a cancer case control study of acute myeloid leukemia recently reported significantly decreased risk in public administration workers from 1988–2007 [Tsai et al, ]. However, German clerical and related office workers had a twofold significant excess of chronic lymphocytic leukemia [Richardson et al, ]; and, an Italian case‐control study found a significant doubling in risk for male office managers and directive clerks [Constantini et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Leukemia mortality was reported to be significantly elevated for several white collar occupations in Washington State, including purchasing agents, buyers managers, sales representatives, and insurance agents during 2000–2010 [Milham and Ossiander, ]. A small New Zealand case‐control study reported that risk was not elevated in administrators and other occupations [McLean et al, ]; and a cancer case control study of acute myeloid leukemia recently reported significantly decreased risk in public administration workers from 1988–2007 [Tsai et al, ]. However, German clerical and related office workers had a twofold significant excess of chronic lymphocytic leukemia [Richardson et al, ]; and, an Italian case‐control study found a significant doubling in risk for male office managers and directive clerks [Constantini et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Registry data have also facilitated preliminary assessment of associations among patient risk factors, including occupational exposures, and health outcomes. For example, industry and occupation data from the California Cancer Registry (CCR) have been used to evaluate the risk of cancer among firefighters, occupations at elevated risk for leukemia subtypes and lung cancer among construction workers; and to assess differences in risk of acute myeloid leukemia by industry and occupation . Given the importance of occupational exposures as risk factors for cancer, the 1992 Cancer Registries Amendment Act (1992 Act) included industrial and occupational (I&O) history among data items required to be collected, if available, for reported incident cases…”
Section: Introductionmentioning
confidence: 99%
“…Environmental and genetic factors are considered to be the most possible risks for AML (5,6). It is likely that many different mutations, epigenetic aberrations and downstream abnormalities are involved in development of AML (7).…”
Section: Introductionmentioning
confidence: 99%